Peningkatan Literasi Keuangan Syariah di Kalangan Mahasiswa untuk Mewujudkan Generasi Ekonomi Muslim Mandiri - Irawan, Feri (Jurnal Aksi Afirmasi, 2024)
This study aims to improve Islamic financial literacy among university students as a strategic step in realizing a generation of independent Muslim economies. Islamic financial literacy, which includes an understanding of the basic principles of Islamic economics, Islamic financial products, as well as personal financial management in accordance with sharia, is considered important in facing modern economic challenges. This study used a qualitative method with a survey approach to students from various universities in Sumbawa. Data was collected through a questionnaire designed to measure the level of understanding and application of Islamic finance among respondents. The results showed that there was a significant increase in Islamic financial literacy after intensive education through seminars, workshops, and learning modules. The findings indicate that improving Islamic financial literacy among university students can contribute to the formation of a generation of Muslim economists who are more independent, intelligent, and ready to face the dynamics of the global economy. The implication of this study is the need for integration of Islamic financial education in the university curriculum as well as increased cooperation between educational institutions and Islamic financial institutions in order to support the development of qualified human resources in the field of Islamic economics.